Analysis of Muslimah Trends on the Consumptive Behavior of Female Students at IAI Hamzanwadi NW East Lombok - M. Khairul Fatihin (Journal of Educational Research and Learning Analytics, 2026)
This qualitative case study deeply investigates the profound impact of modern Muslimah fashion trends and prominent social media influencers on the consumptive behavior of female university students at IAI Hamzanwadi NW East Lombok. Utilizing structured in-depth interviews, participant observations, and interactive qualitative data analysis, this research meticulously explores how contemporary Islamic attire transcends basic theological obligations to become a crucial instrument for academic identity construction and active student engagement. Findings empirically reveal that while digital influencers significantly stimulate consumptive desires, shifting motivations from functional needs to aesthetic lifestyle wants, these female students do not fall into destructive hyperconsumerism today. Instead, they demonstrate an intriguing phenomenon of strictly controlled consumerism. These educated young women critically navigate global digital hegemony by deliberately activating their religious consciousness against wastefulness, prioritizing limited financial capacities, and employing robust digital literacy. Ultimately, educational character resilience successfully moderates impulsive economic behaviors within highly complex modern academic environments.